Biomass for biofuels and value added products innovative technologies towards commercialization of biomass resources for sustainable development in nation building - Mohd Fadzil Mohd Idris (Akademik Kepimpinan Pengajian Tinggi and Penerbit Universiti Malaysia Pahang, 2014)
This publication contains the Proceedings of the International Conference on Biomass for Biofuels and Value Added Products held in Kuala Lumpur on 23-24 October 2012. The theme for this conference was "Innovative Technologies Towards Commercialization of Biomass Resources for Sustainable Development in Nation Building". It is designed to disseminate the latest technology, activities and R&D findings in the utilization of biomass for biofuel and other value-added products to the private sector, researchers, academics, industrialists and policy makers.